Преобразуйте выражение (n^2-2n+1)(n^2+2n+1) в многочлен стандартного вида

1

Ответы и объяснения

  • AlbuRin
  • светило науки
2013-07-11T15:35:44+00:00

(n^2  +  1  -  2n) * (n^2  +  1  +  2n)   применим   формулу  (a -b)*(a + b)  =  a^2  -  b^2,   где

                                                                                                          a  =  n^2  +  1,    b  =  2n

  Получим      (n^2  +  1)^2  -  (2n)^2   =   n^4  +  2n^2  +  1  -  4n^2  =  n^4  -  2n^2  +  1  =

=  (n^2  -  1)^2

 

Ответ.     (n^2  -  1)^2